The Role Of Parents In Appliying Discipline To Children In A Pandemic Period - Melfia, Irena Dara; Setiawan, Andy Wahyu; Izhsanto, Muhammad Reza (Prosiding University Research Colloquium, 2021)
In this era of the COVID-19 pandemic, children are learning online. Therefore, all children activities are also carried out at home, so parents certainly have a big role in student activities at home, one of which is discipline. Discipline is an aspect that must be instilled in children from an early age so that later they can get used to it until adulthood. Without discipline, the child will become someone who has no direction and purpose. Therefore, discipline is very important to be instilled. In this study, the subjects used were parents and children. The purpose of this research is to find out the role of parents in applying discipline to children. The data collection method used is in the form of a literature study. Therefore, data is obtained about the role of parents in applying discipline to children in the pandemic era.